Computational Insights Into the Effects of the R190K and N121Q Mutations on the SARS-CoV-2 Spike Complex With Biliverdin - Qu, Zhiyuan; Li, Kaihang; Geng, Xiaoju; Huang, Bo; Gao, Jian (Frontiers in Molecular Biosciences, 2021)
The SARS-CoV-2 spike has been regarded as the main target of antibody design against COVID-19. Two single-site mutations R190K and N121Q were deemed to weaken the binding affinity of the biliverdin while the underlying molecular mechanism was still unknown. Meanwhile, the effect of the two mutations on the conformational changes of “lip” and “gate” loops was also elusive. Thus, molecular dynamics simulation and MM/GBSA free energy calculation were conducted on the wild type and the other two SARS-CoV-2 spike mutants. Our simulations indicated that the R190K mutation causes Lys190 to form six hydrogen bonds, guided by Asn99 and Ile101, which brings Lys190 closer to Arg102 and Asn121, thereby weakening the interaction energy between the biliverdin and Ile101, Lys190. For the N121Q mutation, Gln121 still maintained a hydrogen bond with biliverdin, nevertheless, the overall binding mode deviated significantly under the reversal of the side chain of Phe175. Moreover, the two mutants would stabilize the lip loop which would restrain the meaningful upward movement of the lip. In addition, N121Q significantly promoted the gate loop deviating to the biliverdin binding site and compressed the site. This work would be useful to understand the dynamics binding of biliverdin to the SARS-CoV-2 spike.